RELATIONSHIP BETWEEN INTERNET MEDIA EXPOSURE AND SEXUAL BEHAVIOUR AMONG YOUNG PEOPLE IN SURAKARTA: 2017/2018 YEAR TWO ENGLISH STUDENTS OF FACULTY OF EDUCATION, SEBELAS MARET UNIVERSITY, SURAKARTA - Chinedu Cletus Agbo (Jurnal Analisa Sosiologi, 2018)
Internet technology nowadays shows a quick progress, and internet media increase their number of users on each day. Social networking, which is one of the main indicators of the internet technology era, attracts people of all ages while the virtual world goes beyond the real life via the applications it offers. Especially young people show an intense interest in internet which is an extension of the media technology. Internet media exposure is increasing both in Indonesia nay Surakarta and all around the world. This study aims to determine the Relationship between Internet Exposure and Sexual Behaviour among young people in Surakarta, and to make suggestions on the prevention of the harmful sexual behavioural effects to the exposure while stating the current work carried out on the subject in Indonesia. Explanatory quantitative cum survey type research model is used in the study, and Internet. In this study, the exposure factor of the Internet Status Scale is used as a data collection tool to measure level of sexual behaviour among young people. The study is conducted on 20 students between the ages of 19-21 with a finding that there is no significant gender difference in internet media exposure even though frequency of exposure and visits had impact on sexual behavior as results showed. Internet Exposure level shows a dramatic increase also in the case of daily time spent on the Internet. The study also provides suggestions on possible actions to prevent harmful sexual behaviour from the exposure. Keywords: Internet Media Exposure, Sexual Behaviour, Relationship, Young people..       AbstrakInternet jaman sekarang menunjukan perkembangan yang cepat, dan media internet meningkatkan jumlah pengguna mereka setiap hari. Jaringan sosial, yang merupakan salah satu indikator utama dari era teknologi internet, menarik orang dari segala usia sementara dunia maya melampaui kehidupan melalui aplikasi itu menawarkan. Khususnya generasi muda menunjukkan minat yang intens di internet yang merupakan perpanjangan dari media teknologi. Eksposur media internet meningkat di Indonesia nay Surakarta maupun di seluruh dunia. Penelitian ini bertujuan untuk menentukan hubungan antara eksposur Internet dan perilaku seksual antara orang-orang muda di Surakarta, dan untuk membuat saran pencegahan efek perilaku seksual berbahaya untuk paparan sambil menyatakan saat ini pekerjaan yang dilakukan keluar pada subjek di Indonesia. Penjelasan kuantitatif cum survei jenis penelitian model digunakan dalam penelitian, dan Internet. Dalam studi ini, faktor paparan Internet Status skala digunakan sebagai data koleksi alat untuk mengukur tingkat perilaku seksual antara orang-orang muda. Kajian dilakukan terhadap 20 siswa berusia antara 19-21 dengan menemukan bahwa tidak ada perbedaan signifikan gender dalam eksposur media internet meskipun frekuensi eksposur dan kunjungan memiliki dampak pada perilaku seksual sebagai hasil menunjukkan. Tingkat pemaparan Internet menunjukkan peningkatan dramatis juga dalam kasus sehari-hari waktu yang dihabiskan di Internet. Studi juga menyediakan saran mungkin tindakan untuk mencegah perilaku seksual yang berbahaya dari eksposur. Kata kunci: Paparan Media Internet, Perilaku Seksual, Hubungan, Orang-Orang Muda